Sociodemographic and health-related factors associated with viral load non-suppression and body mass index in adults with depression symptoms receiving antiretroviral therapy in South Africa - Babalwa Zani; Lara Fairall; Inge Petersen; Naomi Folb; Arvin Bhana; Graham Thornicroft; Jill Hanass-Hancock; Oné Selohilwe; Ruwayda Petrus; Sergio Carmona; Carl Lombard; Crick Lund; et al. (PLoS ONE, 2026)
Introduction While antiretroviral therapy (ART) has significantly improved HIV outcomes, viral load remains unsuppressed for 6% of the people on ART globally in 2024. In South Africa, 5.7 million people are on ART, and viral load non-suppression was reported in 8% of them in 2022. Viral load non-suppression during ART is associated with health decline and HIV transmission. Weight is also a vital component for the management of HIV. High body mass index (BMI) increases the risk of non-communicable diseases, increasing the risk of multimorbidity in people living with HIV. Both ART effectiveness and obesity have been shown to be affected by socioeconomic, psychological and health related factors, but their interrelationships in South Africans living with HIV are not well known. This study aims to investigate the effects of socioeconomic and health related factors at enrolment, and their changes over time in viral load non-suppression and BMI among people receiving ART who have depression symptoms. Methods This was a secondary analysis of data from a randomised controlled trial of depression management in 2002 adults receiving ART. We investigated the effects of sociodemographic characteristics, comorbidities, depression symptoms (Patient Health Questionnaire-9 (PHQ-9)), functional disability (WHODAS-2.0), AIDS-related stigma and ART adherence – all measured at baseline – on viral load non-suppression (viral load ≥1000 copies/ml) and on body mass index (BMI), at baseline and on changes 12 months later, using longitudinal mixed effect logistic and linear regression models. A P-value of 0.05 or less was considered statistically significant. Potentially confounding covariates were selected and adjusted for using least absolute shrinkage and selection operator (LASSO) inference as a sensitivity analysis. Results People with viral load non-suppression at baseline were more likely to be male, younger and to earn lower income. Health characteristics associated with viral load non-suppression at baseline were previous tuberculosis, having been on ART for less than 6 months or more than 10 years, and self-reported non-adherence to ART. Higher disability score and ART duration <6 months or >10 years at baseline were associated with an increasing likelihood of viral load non-suppression 12 months later. Higher BMI at baseline was associated with being female, being married, earning higher income and hypertension, no history of tuberculosis and not having viral load non-suppression. BMI increased from baseline to follow-up, and women and younger people had greater increases in BMI 12 months later. Depression symptom scores and stigma scores were not associated with viral load non-suppression or BMI. Conclusions This study identified sociodemographic risk factors associated with viral non-suppression in PLWH, but most of them were not associated with further changes over time. Functional disability, however, was a risk factor with long-term implications. Younger people and women were at greater risk of BMI increasing over time. This suggests a need for ART programs to integrate long-term support services like frequent adherence assessment, mental health, rehabilitation and weight management strategies tailored to high-risk groups. ClinicalTrials.gov (NCT02407691), Pan African Clinical Trials Registry (201504001078347), South African National Clinical Trials Register (SANCTR) (DOH-27-0515-5048, NHREC 4048).